TEACHING SUBJECT-RELATED COMPETENCIES TO STUDENTS IN SOLVING CHEMISTRY PROBLEMS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the development of subject-related competencies in students during the solving of problems in chemistry lessons.